2021
DOI: 10.1084/jem.20201203
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-induced hepatokine, Manf, ameliorates diet-induced obesity by promoting adipose browning via p38 MAPK pathway

Abstract: Activating beige adipocytes in white adipose tissue (WAT) to increase energy expenditure is a promising strategy to combat obesity. We identified that mesencephalic astrocyte–derived neurotrophic factor (Manf) is a feeding-induced hepatokine. Liver-specific Manf overexpression protected mice against high-fat diet–induced obesity and promoted browning of inguinal subcutaneous WAT (iWAT). Manf overexpression in liver was also associated with decreased adipose inflammation and improved insulin sensitivity and hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…Emerging evidence has now revealed that a number of hepatokines possess a metabolic capacity to regulate a myriad of biological processes in multiple extrahepatic tissues. In addition, hepatokines mediate the physiological benefit and/or influence in certain circumstances, such as exercise [ 238 ] and fasting/refeeding transition [ 239 , 240 ], suggesting that hepatokines can be attractive and important targets for the maintenance of metabolic homeostasis. Hepatokine dysregulation is implicated in the development of NAFLD and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has now revealed that a number of hepatokines possess a metabolic capacity to regulate a myriad of biological processes in multiple extrahepatic tissues. In addition, hepatokines mediate the physiological benefit and/or influence in certain circumstances, such as exercise [ 238 ] and fasting/refeeding transition [ 239 , 240 ], suggesting that hepatokines can be attractive and important targets for the maintenance of metabolic homeostasis. Hepatokine dysregulation is implicated in the development of NAFLD and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a majority of genes altered by WD were equivalently up- or down-regulated across genotypes (Figure 5A-B; Figure S13). Top down-regulated genes included those previously associated with diabetes and obesity, such as Manf 28 and Creld2 29 that facilitate protein folding (Figure 5C), and Igfbp3 and Igfbp7 , two structurally similar proteins that regulate the bioavailability of IGFs and insulin. As noted for WD-fed MR-Intact mice, WD also down-regulated genes associated with extracellular matrix in SMC-MR-KO mice (Figure 5C, Table S13 and 14) and top up-regulated genes also included those implicated in diabetes and obesity, such as Cd36, Txnip, Angptl4, Cyp1a1 , and Fabp4 (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Obesogenic stimuli and HFD may also increase BAT thermogenic capacity to maintain body weight ( García-Ruiz et al, 2015 ). The feeding-induced mesencephalic astrocyte-derived neurotrophic factor was recently shown to ameliorate diet-induced obesity by promoting adipose browning ( Wu et al, 2021 ). A study detected an increased gene expression of P2X7 not only in WAT but also in whitened BAT of diet-induced obesity and ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%